[Obras de Emilio Ambasz]
Se compilan obras del arquitecto y diseñador Emilio Ambasz. Contiene: Housing in an Agricultural Setting, Georgia, USA, 1977. Pro Memoria Garden between Memory and Amnesia, Lndenhausen near Hannover, West Germany, 1978. House for a Couple, Cordoba, Spain, 1978. Residence in a Ravine, Bierges near Brussels, Belginm, 1979. Graphic Design and Exhibition Design.
Keywords: AMBASZ, EMILIO; ESTADOS UNIDOS; GEORGIA; ALEMANIA; HANNOVER; ESPAÑA; BELGICA; BRUSELAS; PABELLONES; VIVIENDAS; VIVIENDAS UNIFAMILIARES; VIVIENDAS RESIDENCIALES; DISEÑO GRAFICO